Prawo własności w nauczaniu episkopatu II Rzeczypospolitej. - Stanulewicz, Maksymilian (Wydawnictwo Poznańskie sp. z o.o., 2012)
The attitudes of Polish Catholic Church hierarchs and the shaping of their views on the fundamental social and economic institutions of the Second Polish Republic were not free from the influence of the Church’s social teaching that developed at the turn of the20th century. One of the key issues that was widely deliberated was that of ownership. In spite of the fact that ownership was a major social institution, it had been for long neglected in the teaching of the Catholic Church in Poland. However, although ignored during the period of Poland’s partitions, once the country regained independence, land ownership issues became suddenly within the interest among Polish bishops, and increased greatly when the government put forward its proposals of reforms in agriculture. The most conservative views and attitudes on land property and the role of land ownership in the social and economic sphere were then activated and, despite the enlightened opinions of some leading Catholic priests in the period 1918-1939 who followed the teaching of Pope Pius XI and advocated fair pay, fighting unemployment, working on social legislation, and the idea subsidiarity and corporate attitudes in economy, the majority of the Polish Episcopate remained steadfast in their utterly conservative convictions, especially on the issue of Church property and its preservation. Thus, the opinions of the few Polish bishops (i.a. Teodor Kubin or Stanisław Adamski) to the contrary were exceptional and isolated, particularly because even the Holy See treated them as too far advanced and modern.

L’évolution de l’enseignement social de l’Église à la charnière des 19ème et 20 ème siècles n’est pas restée sans impact sur l’opinion de la hiérarchie catholique polonaise quant aux principales institutions économiques et sociales sous la 2e République. L’une des questions fondamentales sur laquelle la hiérarchie catholique commence à réfléchir est le sujet de propriété qui, même si c’est une institution sociale de grande importance, s’est trouvée pendant de nombreuses années en dehors du coeur de l’enseignement dispensé par la hiérarchie de l’église catholique polonaise. Bien que le contenu de l’enseignement du pape laisse des évêques souvent indifférents avant la restitution de l’indépendance par le pays, le fait que l’État polonais après sa renaissance ait abordé la problématique de la réforme agraire pousse les évêques à renforcer leurs idées conservatrices en matière de la grande propriété foncière et du rôle social et économique qu’elle jouait. Malgré de nombreux sujets contemporains abordés dans les propos tenus par les principaux hommes de l’église catholique dans les années 1918-1939, conformément au nouvel enseignement de l’époque du pape Pie XI (juste salaire, lutte contre le chômage, réglementation sociale, postulats de subsidiarité de la corporation dans la vie économique), l’Épiscopat de Pologne, dans sa majeure partie tout au moins, est resté intransigeant dans la défense du droit de propriété, notamment des biens possédés par l’Église. Seules les voix de certains évêques, comme celle de Teodor Kubin ou Stanislas Adamski, restent exceptionnellement des voix à part. D’ailleurs, ils ont été considérés comme allant trop loin, même au yeux du Saint-S iège.
Keywords: Prawo własności; II Rzeczpospolita; Episkopat